PEMANFAATAN DAN IDENTIFIKASI TUMBUHAN PAKU (Pteridophyta) - Johanis Manuel Ramandey (Jurnal FAPERTANAK : Jurnal Pertanian dan Peternakan, 2022)
The purpose of this study was to determine the types of ferns and the economic benefits for the Walani people in the MBiandoga District, Intan Jaya Regency. This research This research is descriptive in nature, namely providing descriptive information based on observations and data as well as documentation of the results of research in a systematic and factual manner in the research area. This study uses survey methods and observation methods. According to Usman and Abdi (2009: 30), some experts give the meaning of descriptive research that is broader and includes all kinds of research except historical research and experimental research. In a broad sense, the term survey research is usually used. The data used in this study are primary data and secondary data. The results of this study indicate that (1). There are several types of ferns (Pteridophyta) that grow and live in Danggatadi Village, Biandoga Village and Bugalaga Village. Ferns that live in Danggatadi Village are ferns that have higher soil moisture than ferns that grow in Biandoga Village and Bugalaga Village, where ferns that grow in these two villages need direct sun (not shaded and moist). (2). Ferns (Pteridophyta) are not only useful as vegetables and traditional medicine, but can also increase people's income, especially the Walani people.